Modified electrolyte, preparation method and application thereof
Patent Information
- Application Number
- CN202310783629.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-06-29
AI Technical Summary
Aqueous zinc-ion batteries are prone to hydrogen evolution reaction and dendrite growth during charging and discharging, which leads to reduced coulombic efficiency, reduced zinc utilization, and battery failure.
Bipyridine was used as an electrolyte additive and mixed with zinc sulfate heptahydrate solution to form a modified electrolyte. By changing the solvation structure of zinc ions-water molecules, the hydrogen evolution reaction was inhibited and uniform deposition was guided.
It significantly improves the cycle performance of aqueous zinc-ion batteries, extends battery life, enhances coulombic efficiency, and reduces dendrite growth, thus achieving long battery life and high-efficiency operation.
Smart Images

Figure CN116683047B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrolyte preparation technology, and in particular to a modified electrolyte, its preparation method, and its application. Background Technology
[0002] Human industrialization and social development require vast amounts of energy, but the increasing use of fossil fuels inevitably leads to a series of environmental problems, such as the greenhouse effect and acid rain. To address this crisis, actively adjusting the energy structure is one of the effective means to alleviate the current predicament. Increasing the proportion of renewable energy can both meet the energy needs of production and efficiently address environmental issues. Renewable energy is generally available and clean, but its storage and transportation pose challenges to commercialization. In this regard, energy storage systems are crucial. In existing energy storage systems, batteries play an indispensable role.
[0003] Aqueous zinc-ion batteries (AZIBs) are valued for their high theoretical capacity (820 mAh·g). -1 5854mAh·cm -3 Zinc-ion batteries, with their low redox potential (-0.762V vs. SHE), high safety, and abundant reserves, have become a popular choice for large-scale energy storage systems. However, the main obstacles to the commercial application of aqueous zinc-ion batteries are: ① Hydrogen evolution reaction (HER): Compared to the standard hydrogen electrode potential, Zn... 2+ The redox potential of zinc (Zn) is -0.762V vs. SHE. During battery charge-discharge cycles, hydrogen evolution inevitably occurs, leading to a local pH increase and the generation and accumulation of basic zinc sulfate. This results in reduced coulombic efficiency, decreased zinc utilization, and reduced reversibility. Simultaneously, the continuously generated hydrogen gas eventually causes battery bulging, leading to battery failure. ② Dendrite growth: Due to the uneven distribution of charge on the zinc electrode surface and zinc ion concentration at the electrode-electrolyte interface, localized areas become dominant nucleation sites, causing uneven electrodeposition. Subsequently, electrodeposition is affected by the "tip effect," forming a larger current density at the "tip," further promoting dendrite growth. Ultimately, dendrites penetrate the separator, causing a short circuit in the battery.
[0004] To date, numerous excellent strategies have been developed to address the current predicament, including surface modification, electrolyte engineering, and negative electrode structure optimization. Surface modification, by altering the electrode-electrolyte contact state, guides zinc ion deposition and mitigates the degree of side reactions. Guo (Hao J, Li B, Li X, et al. An in-depth study of Zn metal surface chemistry for advanced daqueous Zn-ion batteries[J]. Advanced Materials, 2020, 32(34): 2003-021) et al. used chemical vapor deposition (CVD) to react sulfur vapor with zinc foil at 350 °C to generate a ZnS layer in situ, which acts as a physical barrier to inhibit zinc metal corrosion and guides uniform zinc ion deposition under SEI to achieve dendrite-free behavior. Li (Xiao P, Li H, Fu J, et al. An anticorrosive zinc metal anode with ultra-long cycle life over one year[J]. Energy & Environmental Science, 2022, 15(4): 1638-1646) et al. used a chemical substitution method to replace an indium metal layer on the surface of zinc foil. After indium modification, the hydrogen evolution potential shifted to a negative potential, suppressing the hydrogen evolution reaction and achieving a long battery life. Ji (Liu C, Luo Z, Deng W, et al. Liquid alloy interlayer foraqueous zinc-ion battery[J]. ACS Energy Letters, 2021, 6(2): 675-683) et al. used a blade coating method to coat Ga-In liquid alloy onto the zinc anode, realizing a liquid-liquid alloy-electrolyte interface with fast electron / mass transport. At the same time, the increase in the hydrogen evolution reaction (HER) overpotential enhanced corrosion resistance. Electrolyte engineering aims to induce uniform zinc deposition by adjusting ion flux or solvation structure. Yang (Li R, Li M, Chao Y, et al. Hexaoxacyclooctadecane induced interfacial engineering to achieved endrite-free Zn ion batteries[J]. Energy Storage Materials, 2022, 46: 605-612) et al. added 18-crown ether-6 to the typical electrolyte ZnSO4. The inner ring of the crown ether can form a stable complex with metal ions, thereby regulating the zinc ion deposition flux, while the hydrophobicity of the outer ring can suppress hydrogen evolution.Hu (Wang H, Ye W, Yin B, et al. Modulating cation migration and deposition with xylitol additive and oriented reconstruction of hydrogen bonds for stable zinc anodes[J]. Angewandte Chemie, 2023, 135(10):e202218872) et al. chose xylitol as an additive for ZnSO4 electrolyte to reduce solvation of water molecules by directional reconstruction of hydrogen bonds, while preferentially adsorbing on Zn plates to prevent 2D diffusion of ions at the zinc-electrolyte interface. Yu (Li M, Xi C, Wang X, et al. Spontaneous Desaturation of the Solvation Sheath for High-Performance Anti-Freezing Zinc-Ion Gel-Electrolyte[J]. Small, 2023:2301569) et al. designed a water-organic hybrid gel electrolyte based on polyvinyl alcohol, which achieved spontaneous desaturation solvation structure at room temperature or even low temperature to reduce hydrogen evolution and dendrite growth. Anode structure optimization tends to reduce local current density or provide specific crystal orientations to guide epitaxial deposition. Pu et al. (Guo W, Cong Z, Guo Z, et al. Dendrite-free Zn anode with dual channel 3D porous frameworks for rechargeable Zn batteries[J]. Energy Storage Materials, 2020, 30: 104-112) developed a 3D nanoporous zinc anode using an electrodeposition-sintering process. During electroplating / stripping, the 3D porous structure can significantly reduce the surface current density, promote uniform Zn deposition, and suppress dendrite growth. Alex W. Robertson (Pu SD, Gong C, Tang Y T, et al. Achieving Ultrahigh-Rate Planar and Dendrite-Free Zinc Electroplating for Aqueous Zinc Battery Anodes[J]. Advanced Materials, 2022, 34(28): 2202552) et al. used (002) single-crystal zinc metal as the anode and utilized a lattice matching strategy to achieve epitaxial zinc growth along the (002) crystal plane.
[0005] Unlike other strategies, electrolyte additives are one of the most promising means to promote the successful commercialization of aqueous zinc-ion batteries because of their advantages such as low cost and simple experimental operation. Current research on additives tends to modify the solvation structure of zinc ions, occupying the water molecule positions in the zinc ion-water molecule solvation structure to reduce the hydrogen evolution process. However, such work often requires a large amount of additives, which undoubtedly undermines the low cost advantage of aqueous zinc-ion batteries.
[0006] Therefore, developing a low-cost modified electrolyte is an important research direction for improving the adverse reactions of aqueous zinc-ion batteries. Summary of the Invention
[0007] The purpose of this invention is to provide a modified electrolyte, its preparation method, and its application, to solve the problems of hydrogen evolution reaction and dendrite growth that easily occur in existing aqueous zinc-ion batteries.
[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0009] The present invention provides a modified electrolyte comprising an electrolyte, a solvent, and an additive, wherein the electrolyte is zinc sulfate heptahydrate, the solvent is water, and the additive is bipyridine.
[0010] Furthermore, in the modified electrolyte, the molar ratio of the electrolyte to the additive is 1:0.005 to 0.05.
[0011] Furthermore, in the modified electrolyte, the ratio of solvent to electrolyte is 4.37 mL: 1.4378–2.8756 g.
[0012] The present invention also provides a method for preparing a modified electrolyte, comprising the following steps: mixing an electrolyte, a solvent and an additive to obtain a modified electrolyte.
[0013] Furthermore, in the method for preparing the modified electrolyte, the electrolyte, solvent, and additive are mixed as follows: the electrolyte and solvent are mixed to obtain an electrolyte solution; the additive is added to the electrolyte solution and stirred.
[0014] Furthermore, in the method for preparing the modified electrolyte, the stirring temperature is 15–25°C, the stirring time is 6–12 h, and the stirring speed is 800–1500 r / min.
[0015] The present invention also provides the application of a modified electrolyte or a modified electrolyte prepared by a method thereof in an aqueous zinc-ion battery, wherein the aqueous zinc-ion battery comprises a positive electrode, a negative electrode, a separator and a modified electrolyte.
[0016] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The present invention uses bipyridine as an electrolyte additive to synthesize a novel modified electrolyte in zinc sulfate solution, which can effectively improve the cycle performance of aqueous zinc-ion batteries.
[0018] (2) The equipment and chemical reagents used in this invention are readily available, the process conditions are simple, the operation is convenient, the cost is low, the industrial application value is high, and the application value is great. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0020] Figure 1 The LSV diagrams are for the electrolytes obtained in Examples 1-4 and Comparative Example 1.
[0021] Figure 2 The differential capacitance diagrams are shown for the electrolytes obtained in Example 2 and Comparative Example 1.
[0022] Figure 3 Tafel diagrams of the electrolytes obtained in Example 2 and Comparative Example 1;
[0023] Figure 4 The contact angle of 1MZSO, 10mM2,2-BPY, and the modified electrolyte obtained in Example 2 on a zinc metal substrate, wherein 1MZSO is a 1mol / L ZnSO4 solution and 10mM2,2-BPY is a 10mmol / L bipyridine solution;
[0024] Figure 5 For application examples 1-4, compare the symmetrical cells obtained in application example 1 at 1 mA cm⁻¹ -2 1mAhcm -2 A graph showing the number of iterations under given conditions;
[0025] Figure 6 To illustrate the application of Example 2 and compare it with the symmetrical cells obtained in Examples 1-3, the 1 mA cm⁻¹ -2 1mAhcm -2 A graph showing the number of iterations under given conditions;
[0026] Figure 7 For application examples 1-4, compare the symmetrical cells obtained in application example 1 at 5 mA / cm. -2 1mAhcm -2 A graph showing the number of iterations under given conditions;
[0027] Figure 8 For application examples 1-4, and in comparison with the zinc-copper battery obtained in application example 1, the performance at 1 mA / cm² is as follows: -2 1mAhcm -2 Coulomb efficiency diagram under the given conditions;
[0028] Figure 9 Example 2 is used to compare the cycle capacity graph of the full cell obtained in Example 1 under the test rate of 0.5C.
[0029] Figure 10 The XRD patterns are of zinc electrodes obtained from Example 2 after 10, 25, and 50 cycles of the symmetrical battery, and of zinc electrodes for which the battery cycle performance was not tested. Detailed Implementation
[0030] The present invention provides a modified electrolyte comprising an electrolyte, a solvent, and an additive, wherein the electrolyte is zinc sulfate heptahydrate, the solvent is water, and the additive is bipyridine.
[0031] In this invention, the molar ratio of the electrolyte to the additive is preferably 1:0.005 to 0.05, more preferably 1:0.01 to 0.02, and even more preferably 1:0.01.
[0032] In this invention, the preferred ratio of solvent to electrolyte is 4.37 mL: 1.4378–2.8756 g, more preferably 4.37 mL: 1.4378–2.1567 g, and even more preferably 4.37 mL: 1.4378 g.
[0033] In this invention, the water is ultrapure water.
[0034] The present invention also provides a method for preparing a modified electrolyte, comprising the following steps: mixing an electrolyte, a solvent and an additive to obtain a modified electrolyte.
[0035] In this invention, the preferred method for mixing the electrolyte, solvent, and additive is to mix the electrolyte with the solvent to obtain an electrolyte solution; and then add the additive to the electrolyte solution and stir.
[0036] In this invention, the stirring temperature is preferably 15-25°C, more preferably 18-22°C, and even more preferably 20°C.
[0037] In this invention, the stirring time is preferably 6 to 12 hours, more preferably 10 to 12 hours, and even more preferably 12 hours.
[0038] In this invention, the stirring speed is preferably 800-1500 r / min, more preferably 1300-1500 r / min, and even more preferably 1500 r / min.
[0039] The present invention also provides the application of a modified electrolyte or a modified electrolyte prepared by a method thereof in an aqueous zinc-ion battery, wherein the aqueous zinc-ion battery comprises a positive electrode, a negative electrode, a separator and a modified electrolyte.
[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] Example 1
[0042] This embodiment provides a method for preparing a modified electrolyte, including the following steps:
[0043] 1.4378 g of zinc sulfate heptahydrate was added to 4.37 mL of ultrapure water and stirred thoroughly to obtain a clear solution with a zinc sulfate concentration of 1 mol / L. Then, 0.003905 g of dipyridine was added to the above solution and stirred at 1500 r / min for 12 h at 20 °C to obtain a homogeneous and transparent modified electrolyte with a dipyridine concentration of 0.005 mol / L, denoted as Add5mM2,2-BPY.
[0044] Example 2
[0045] The difference between Example 2 and Example 1 is that 0.00781g of bipyridine was added, and other conditions were the same as in Example 1, resulting in a modified electrolyte with a bipyridine concentration of 0.01mol / L, denoted as Add10mM2,2-BPY.
[0046] Example 3
[0047] The difference between Example 3 and Example 1 is that 0.011715g of bipyridine was added, and other conditions were the same as in Example 1, resulting in a modified electrolyte with a bipyridine concentration of 0.015mol / L, denoted as Add15mM2,2-BPY.
[0048] Example 4
[0049] The difference between Example 4 and Example 1 is that 0.01562g of bipyridine was added, and other conditions were the same as in Example 1, resulting in a modified electrolyte with a bipyridine concentration of 0.02mol / L, denoted as Add20mM2,2-BPY.
[0050] Comparative Example 1
[0051] This comparative example provides an electrolyte, including the following steps:
[0052] 1.4378 g of zinc sulfate heptahydrate was added to 4.37 mL of ultrapure water and stirred thoroughly to obtain an electrolyte with a zinc sulfate concentration of 1 mol / L, denoted as 1 MZSO.
[0053] Comparative Example 2
[0054] The difference between Comparative Example 2 and Example 1 is that the bipyridine was replaced with 2,6-pyridinedicarboxylonite, and the amount added was 0.0065 g. Other conditions were the same as in Example 1, and a modified electrolyte with a concentration of 0.01 mol / L of 2,6-pyridinedicarboxylonite was obtained, which was denoted as Add10mMPy-DB.
[0055] Comparative Example 3
[0056] The difference between Comparative Example 3 and Example 1 is that bipyridine was replaced with pyridine, and the amount added was 0.00396g. Other conditions were the same as in Example 1, resulting in a modified electrolyte with a pyridine concentration of 0.01mol / L, denoted as Add10mMPy.
[0057] Figure 1 The LSV diagrams for the electrolytes obtained in Examples 1-4 and Comparative Example 1 are shown. From the hydrogen evolution potential (HEP) in the diagrams, the modified electrolyte of Example 2 with 10 mM bipyridine has an HEP of 1.364 (Vvs.Ag / AgCl), while the electrolyte of Comparative Example 1 without additives has an HEP of 1.052 (Vvs.Ag / AgCl). The leftward shift in the HEP reflects that the HEP reaction is effectively suppressed when the additive is present; and the HEP reaction is suppressed to the greatest extent when the additive concentration is 10 mM.
[0058] Figure 2 The differential capacitance diagrams for the electrolytes obtained in Example 2 and Comparative Example 1 show that, compared to the larger capacitance value of the electrolyte surface without the addition of bipyridine in Comparative Example 1, the capacitance value of the electrode surface of the modified electrolyte in Example 2 is significantly reduced after bipyridine is added as an additive. This indicates that the bipyridine macromolecules are attached to the electrode surface, resulting in a smaller gap between the double-layer capacitors and a decrease in the overall capacitance value, proving the successful adsorption of bipyridine.
[0059] Figure 3 The Tafel plots of the electrolytes obtained in Example 2 and Comparative Example 1 show that the modified electrolyte with the addition of 10 mM bipyridine additive exhibits a significantly increased Tafel slope and a significantly decreased exchange current density. Therefore, the presence of the bipyridine additive effectively improves the corrosion of zinc metal.
[0060] Figure 4The contact angles of the modified electrolytes obtained in Example 2 (1MZSO, 10mM 2,2-BPY) on a zinc metal substrate are shown. The contact angle of the 1MZSO solution on the zinc metal substrate is 80.73°, the contact angle of the 10mM pure bipyridine solution on the zinc metal substrate is 48.42°, and the contact angle of the modified electrolyte with 10mM bipyridine added in Example 2 on the zinc metal substrate is 49.31°. It can be seen that the presence of additives brings better interfacial contact to the electrolyte, which will be beneficial to the ion transfer of the interfacial reaction.
[0061] Application Example 1
[0062] Preparation of symmetrical cells: 180 μL of the modified electrolyte obtained in Example 1 was dropped onto a glass fiber separator. The symmetrical cells were assembled in the following order: negative electrode shell - zinc foil - separator - electrolyte - zinc foil - gasket - spring sheet - positive electrode shell. Sealing was performed using a small hydraulic button cell packaging machine (MSK-110). The packaging pressure of the button cell packaging machine needed to be greater than 50 kg / cm². 3 The duration is 10 seconds.
[0063] Preparation of zinc-copper batteries: 180 μL of the modified electrolyte obtained in Example 1 was dropped onto a glass fiber separator, and the zinc-copper battery was assembled in the following order: negative electrode shell - zinc foil - separator - electrolyte - copper foil - gasket - spring sheet - positive electrode shell. The encapsulation pressure and duration after battery assembly were the same as those used in the preparation of symmetrical electrodes.
[0064] Application Example 2
[0065] Preparation of symmetric cells: Replace 180 μL of the modified electrolyte obtained in Example 1 with 180 μL of the modified electrolyte obtained in Example 2, and keep other conditions the same as in Application Example 1.
[0066] Preparation of zinc-copper batteries: Replace 180 μL of the modified electrolyte obtained in Example 1 with 180 μL of the modified electrolyte obtained in Example 2, and keep other conditions the same as in Application Example 1.
[0067] Preparation of the full cell: 180 μL of the modified electrolyte obtained in Example 2 was dropped onto a glass fiber separator. The full cell was assembled in the following order: negative electrode shell - zinc foil - separator - electrolyte - positive electrode (VO2) - gasket - spring sheet - positive electrode shell. The encapsulation pressure and duration after battery assembly were the same as those for preparing symmetrical electrodes. The difference from preparing symmetrical cells is that paper needs to be placed on top when encapsulating the full cell to prevent the formation of a circuit outside the cell during encapsulation. Furthermore, the newly encapsulated full cell cannot be used immediately; it needs to stand for at least 2 hours to allow sufficient contact between the electrode and electrolyte interfaces before testing.
[0068] Application Example 3
[0069] Preparation of symmetric cells: Replace 180 μL of the modified electrolyte obtained in Example 1 with 180 μL of the modified electrolyte obtained in Example 3, and keep other conditions the same as in Application Example 1.
[0070] Preparation of zinc-copper batteries: Replace 180 μL of the modified electrolyte obtained in Example 1 with 180 μL of the modified electrolyte obtained in Example 3, and keep other conditions the same as in Application Example 1.
[0071] Application Example 4
[0072] Preparation of symmetric cells: Replace 180 μL of the modified electrolyte obtained in Example 1 with 180 μL of the modified electrolyte obtained in Example 4, and keep other conditions the same as in Application Example 1.
[0073] Preparation of zinc-copper batteries: Replace 180 μL of the modified electrolyte obtained in Example 1 with 180 μL of the modified electrolyte obtained in Example 4, and keep other conditions the same as in Application Example 1.
[0074] Comparative Application Example 1
[0075] Preparation of symmetric cells: Replace 180 μL of the modified electrolyte obtained in Example 2 with 180 μL of the modified electrolyte obtained in Comparative Example 1, and keep other conditions the same as in Application Example 2.
[0076] Preparation of zinc-copper batteries: Replace 180 μL of the modified electrolyte obtained in Example 2 with 180 μL of the modified electrolyte obtained in Comparative Example 1, and keep other conditions the same as in Application Example 2.
[0077] Preparation of full cells: Replace 180 μL of the modified electrolyte obtained in Example 2 with 180 μL of the modified electrolyte obtained in Comparative Example 1, and keep other conditions the same as in Application Example 2.
[0078] Comparative Application Example 2
[0079] Preparation of symmetric cells: Replace 180 μL of the modified electrolyte obtained in Example 2 with 180 μL of the modified electrolyte obtained in Comparative Example 2, and keep other conditions the same as in Application Example 2.
[0080] Comparative Application Example 3
[0081] Preparation of symmetric cells: Replace 180 μL of the modified electrolyte obtained in Example 2 with 180 μL of the modified electrolyte obtained in Comparative Example 3, and keep other conditions the same as in Application Example 2.
[0082] The battery test of this invention was conducted using the CT-4008T battery tester from Shenzhen Xinwei New Energy Technology Co., Ltd., and the tested battery was a CR2032 button cell battery.
[0083] The symmetrical battery was tested using a constant current charge-discharge method with a test current of 5 mA / cm². 2and 1.0 mA / cm 2 The time was 12 min and 60 min. The dendrite growth state inside the symmetrical cell was indirectly determined by the voltage change and the number of cycles during the long-term charge / discharge process.
[0084] The zinc-copper battery was tested using a constant current charge-discharge method, with a test current of 1.0 mA / cm². 2 The capacity is 1.0mAh / cm³. 2 The degree of side reactions occurring inside zinc-copper batteries is determined by the charge-discharge efficiency and the number of cycles during long-term discharge and charge processes.
[0085] After the positive electrode of the full battery is installed, rate performance testing can be performed at a rate of 0.5C. By analyzing the specific capacity before and after full battery cycling, performance indicators such as coulombic efficiency and rate charge / discharge performance can be obtained to judge the battery performance under actual working conditions.
[0086] Figure 5 For application examples 1-4, compare the symmetrical cells obtained in application example 1 at 1 mA cm⁻¹ -2 1mAhcm -2 The cycle life graph under the above test conditions is shown. Compared with Application Example 1, which uses 1 MZSO electrolyte and has a cycle life of only more than 70 hours, Application Example 2, which uses 10 mM bipyridine modified electrolyte, successfully extended the cycle life of the symmetric battery to 4000 hours.
[0087] Figure 6 To illustrate the application of Example 2 and compare it with the symmetrical cells obtained in Examples 1-3, the 1 mA cm⁻¹ -2 1mAhcm -2 The cycle count graph under the specified conditions shows that, at 86 hours, the symmetric cell in Comparative Application Example 3 with the addition of 10 mM pyridine experienced a short circuit. This is because the extremely small amount of pyridine did not alter the zinc ion deposition behavior. For the symmetric cell in Comparative Application Example 2 with the addition of 10 mM 2,6-pyridinedicarboxynitrile, a severe hydrogen evolution reaction occurred around 110 hours, resulting in unstable electroplating / stripping behavior. In contrast, the symmetric cell in Application Example 2, after adding the modified electrolyte of 10 mM dipyridine, could operate stably for 4000 hours, highlighting the superior performance and irreplaceable nature of dipyridine.
[0088] Figure 7 For application examples 1-4, compare the symmetrical cells obtained in application example 1 at 5 mA / cm. -2 1mAhcm -2The cycle life graph under the given conditions shows that the symmetric cell in Application Example 2 using 10 mM bipyridine modified electrolyte has a cycle life of over 2200 cycles, while the symmetric cell in Comparative Application Example 1 using 1 MZSO electrolyte has a cycle life of only 220 cycles. It can be seen that even under high current, the modified electrolyte with bipyridine additive exhibits a good cycle life.
[0089] Figure 8 For application examples 1-4, and in comparison with the zinc-copper battery obtained in application example 1, the performance at 1 mA / cm² is as follows: -2 1mAhcm -2 The coulombic efficiency diagram under the specified conditions is compared with that of the zinc-copper battery in Application Example 1, which failed after more than 100 cycles using 1 MZSO electrolyte, while the zinc-copper battery in Application Example 2, which used 10 mM bipyridine modified electrolyte, operated stably for more than 400 cycles and had an average coulombic efficiency of 99.5%.
[0090] Figure 9 To compare the cycle capacity graph of the full cell obtained in Application Example 2 with that in Application Example 1 under a test rate of 0.5C, VO2 was used as the positive electrode material. As can be seen from the graph, the full cell in Application Example 2 using 10mM bipyridine modified electrolyte has a better capacity retention rate after 400 cycles.
[0091] Figure 10 The XRD patterns of zinc electrodes obtained from Example 2 after 10, 25, and 50 cycles of the symmetrical battery and zinc electrodes without battery cycle performance testing are shown. By comparing the crystal orientation of the zinc deposited layer after different number of cycles, it can be determined how the metal tends to deposit during the deposition process. From the XRD patterns, it can be seen that as the number of cycles increases, zinc tends to deposit on the (002) crystal plane. As is well known, deposition along the (002) crystal plane will form a planar stepped morphology on the microscopic level and exhibit a flat and smooth deposition layer on the macroscopic level, thereby reducing the generation of dendrites.
[0092] In summary, this invention successfully enabled a symmetrical battery to operate at 1 mA / cm² using bipyridine as an electrolyte additive at a dosage of only 10 mM. -2 1mAhcm -2 Under these conditions, the cycle life is extended to 4000 hours (compared to only 70+ hours for traditional electrolyte 1MZSO), at 5mAcm -2 1mAhcm -2Under certain conditions, the battery achieved over 2200 cycles (compared to only 220 cycles with conventional electrolyte 1MZSO), with an average coulombic efficiency of 99.5%. It also performed well in full cells with VO2 as the positive electrode. During cycling, bipyridine preferentially adsorbs onto different crystal planes of the zinc foil, acting as a small-molecule "shielding layer," altering the original electric double-layer structure and occupying the positions of active water molecules at the solid-liquid interface, thus reducing water molecule decomposition. Simultaneously, due to the different surface energies of different zinc metal crystal planes, the adsorption energy of bipyridine varies on different crystal planes. XRD analysis of the electrodes after different cycles shows that the presence of bipyridine molecules causes zinc ions to preferentially deposit on the (002) crystal plane, achieving specific deposition on the (002) crystal plane, reducing dendrite formation, and achieving a long lifespan for the zinc-ion battery.
[0093] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A modified electrolyte, said modified electrolyte comprising an electrolyte, a solvent, and additives, characterized in that, The electrolyte is zinc sulfate heptahydrate, the solvent is water, and the additive is bipyridine; The molar ratio of the electrolyte to the additive is 1:0.005~0.05; The ratio of the solvent to the electrolyte is 4.37 mL: 1.4378~2.8756 g.
2. The method for preparing the modified electrolyte according to claim 1, characterized in that, Includes the following steps: The electrolyte, solvent, and additives are mixed to obtain a modified electrolyte.
3. The method for preparing the modified electrolyte as described in claim 2, characterized in that, The electrolyte, solvent, and additive are mixed as follows: the electrolyte and solvent are mixed to obtain an electrolyte solution; the additive is then added to the electrolyte solution and stirred.
4. The method for preparing the modified electrolyte as described in claim 3, characterized in that, The stirring temperature is 15~25℃, the stirring time is 6~12h, and the stirring speed is 800~1500r / min.
5. The application of the modified electrolyte prepared by the method of claim 1 or any one of claims 2-4 in an aqueous zinc-ion battery, characterized in that, The aqueous zinc-ion battery includes a positive electrode, a negative electrode, a separator, and a modified electrolyte.
Citation Information
Patent Citations
Aqueous zinc ion electrolyte additive and application thereof
CN115133153A
